Elaboration of the system of competences of environmental monitoring in future specialists - Бордюг, Наталія Сергіївна (ScienceRise: Pedagogical Education, 2016)
The necessity of elaboration of the system of diagnostics of competences of environmental monitoring in future specialists is elucidated in the article. The types and methods of control, on which base has been formed the structural-logic scheme of their use at the study of discipline “Environmental monitoring”, were characterized. Three levels of control were separated in the system of diagnostics of competences of environmental monitoring were separated: income, intermediate, final – their problem-thematic coordination was established in means and diagnostic criteria. The means of diagnostics of competences were improved at realization of creative, individual, scientific works of students that at first can be presented as formed interdisciplinary course project and in further – qualified diploma work that can solve the complex environmental problems, typical for the local system “Little Motherland”, of one student in particular or of the target group of students (for the solution of problems by the types nature management in the fields of economy by the types of economic activity). It was studied, that at the expanse of using the competence approach in professional preparation of future specialists the training quality is provided with potential possibilities of its correction according to the three of aims at organization of learning-upbringing process, especially realization of individual and differential approaches in learning-cognitive and scientific activity to satisfy the socio-environmental demand of society in high-qualified specialists, able to solve professional tasks of different environmental complication and to model the environmental situation on the principles of steadiness